Study on Morphological Properties of Polyvinyl Alcohol/Poly(lactic acid) Wound Dressing Membrane as Drug Delivery Carrier in Wound Healing Treatment - Ng, Celine; Hamzah, Mohd Syahir Anwar; Abd Razak, Saiful Izwan; Abdul Sukor, Jumadi; Nayan, Nafarizal; Mat Nayan, Nadirul Hasraf (Journal of Advanced Industrial Technology and Application, 2020)
Wound dressing have experienced continuous improvement and changes since ancient time. Electrospinning of polymeric nanofibers have captured the interest of researchers due to its simplicity and cost effective technique that able to produce wound dressing membrane that meet the requirement as ideal wound dressing and drug delivery carrier. In this work, polyvinyl alcohol (PVA) and poly (lactic acid) (PLA) were chosen polymer to produce wound dressing membrane through electrospinning and coating method. PVA was electrospun and then coated with PLA. The aim of this study was to investigate the morphological properties of PVA/PLA wound dressing membrane. Based on the results from Atomic Force Microscope, PVA nanofiber coated with 4% PLA exhibit the highest value of Rq which is 0.47 Â± 0.19 Î¼m compared to neat PVA nanofibers membrane. Field Emission Scanning Electron Microscope (FE-SEM) image revealed that PVA nanofiber coated with 4% PLA shows porous fiber-like morphology and well incorporated with each other without any gap formed between them. This report clearly suggestive of the fact that synthetic biodegradable polymers such as PLA can be exploited for the synergistic combination with PVA nanofiber for wound dressing application.